Biomedical studies on temporal bones of the first multi-channel cochlear implant patient at the University of Melbourne. (September 2014) - Clark, Graeme M; Clark, Jonathan; Cardamone, Tina; Clarke, Maria; Nielsen, Prue; Jones, Rob; Arhatari, Benedicta; Birbilis, Nick; Curtain, Roger; Xu, Jin; Wagstaff, Sheryl; Gibson, Peter; et al.
Abstract : Objective: To analyse the temporal bones and implant of the first University of Melbourne's (UOM) patient (MC-1) to receive the multi-channel cochlear prosthesis. Methods: The left cochlea was implanted with the prototype multi-channel cochlear prosthesis on 1 August 1978, and the Cochlear versions CI-22 and CI-24 on 22 June 1983 and 10 November 1998, respectively. MC-1 died in 2007. Results: Plain X-rays of the temporal bones showed that after the CI-22 had been explanted seven electrode bands remained in situ. Micro-CT scans also revealed a partially united fracture transecting the left implanted and right control cochleae. Histology indicated a total loss of the organ of Corti on both sides, and a tear of the left basilar membrane. In addition, there was a dense fibrous capsule with heterotopic bone surrounding one proximal band of the CI-22 array that restricted its removal. This pathology was associated with dark particulate material within macrophages, probably due to the release of platinum from the electrode bands. Scanning electron microscopy (SEM) showed possible corrosion of platinum and surface roughening. Three-dimensional reconstruction of the cochlear histology demonstrated the position of the electrode tracts (C1-22 and CI-24) in relation to the spiral ganglion, which showed 85–90% loss of ganglion cells. Discussion and conclusions: This study confirms our first histopathological findings that our first free-fitting banded electrode array produced moderate trauma to the cochlea when inserted around the scala tympani of the basal turn. The difficulty in extraction was most likely due to one band being surrounded by an unusually large amount of fibrous tissue and bone, with an electrode band caught due to surface irregularities. Some surface corrosion and a small degree of platinum deposition in the tissue may also help explain the outcome for this long-term cochlear implantation.